Indian economy: performance review-1947-48 to 2010-11 - Prasad, Chandra Shekhar (New Delhi, 2010)
This book provides a comprehensive description and analysis of economic policies, strategies, challenges and achievements in various sectors of the Indian economy over the years.
Keywords: Indian economy-1947-48 to 2010-11